A new car-following model with consideration of roadside memorial - Tang, T.; Wu, Yong Hong; Caccetta, Louis; Huang, H. (Elsevier Science BV, 2011)
In this Letter, a car-following model with consideration of roadside memorial is proposed. The numerical results show that the proposed model can qualitatively describe the impacts of roadside memorial on traffic flow and the traffic risk coefficient. It is also shown that roadside memorial can enhance the traffic safety.